Effect of cutting parameters and tool coating on residual stress and cutting temperature in dry hard turning of AISI 52100 steel using finite element method - Mane, Sandip; Patil, Rajkumar Bhimgonda; Siddiqui, Md Irfanul Haque; Chan, Choon Kit; Xu, Yong (Frontiers in Materials, 2025)
Hard turning is a high-precision machining approach widely adopted in manufacturing for finishing hardened alloy steels that exhibit superior hardness and excellent wear resistance. The residual stresses induced during the hard turning process significantly impact the performance and reliability of the machined component. This study presents a comprehensive finite element analysis to predict residual stress distribution and thermal behavior during dry hard turning of AISI 52100 steel under varying cutting conditions. The Power Law material model, incorporating a strain hardening function, was employed to simulate the material’s behavior at high strain rates, accounting for strain rate sensitivity and thermal softening due to elevated temperatures during machining. The model further includes a Coulomb friction approach to capture the interactions between the tool, chip, and workpiece. The cutting speed was found to have the most significant impact on surface tensile stresses. The subsurface residual stresses were greatly affected by the feed rate. The elevated feed rates resulted in increased compressive residual stresses being induced in the machined component. The developed FEM model demonstrated its effectiveness as an essential tool for pre-processing residual stress predictions, which in turn helps in the design and manufacture of reliable, high-quality, components. The thermal performance of coated carbide tools; more specifically, the performance of titanium nitride (TiN), titanium carbonitride (TiCN), and aluminum oxide (Al2O3) coating layers were examined. Tools coated with multilayer structures incorporating Al2O3 as the top layer demonstrated superior thermal barrier performance, leading to a notable reduction in both heat generation and maximum cutting temperatures. The cutting temperature data recorded using embedded thermocouple technique with infrared thermometers showed a good agreement with the FEM results. This validation confirms the AdvantEdge’s simulation precision and enhances understanding of machining dynamics, contributing to robust component design with superior surface integrity.